2020
DOI: 10.1186/s12933-020-01094-5
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acid supplementation versus placebo on vascular health, glycaemic control, and metabolic parameters in people with type 1 diabetes: a randomised controlled preliminary trial

Abstract: Background: The role of omega-3 polyunsaturated fatty acids (n-3PUFA), and the potential impact of n-3PUFA supplementation, in the treatment and management of type 1 diabetes (T1D) remains unclear and controversial. Therefore, this study aimed to examine the efficacy of daily high-dose-bolus n-3PUFA supplementation on vascular health, glycaemic control, and metabolic parameters in subjects with T1D. Methods: Twenty-seven adults with T1D were recruited to a 6-month randomised, double-blind, placebo-controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…This could reflect the nutritional advice strategies performed in T1D patients in our geographical area, which are focused on the adaptation of a Mediterranean-style eating pattern with high fish consumption [28]. Furthermore, our findings seem to agree with a recent randomized controlled trial in which high doses of n-3 PUFAs (EPA + DHA, 3.3 g/day) over a 6-month period did not decrease carotid intima-media thickness or other measures of vascular function (artery flow mediated dilatation) in patients with T1D [44]. Notwithstanding, it cannot be ruled out that very high doses (i.e., 4 g/day) of a specific n-3 PUFA (EPA) over a long time period (i.e., REDUCE-IT trial [45]) could be beneficial for CVD prevention in this specific high-risk population.…”
Section: Discussionsupporting
confidence: 91%
“…This could reflect the nutritional advice strategies performed in T1D patients in our geographical area, which are focused on the adaptation of a Mediterranean-style eating pattern with high fish consumption [28]. Furthermore, our findings seem to agree with a recent randomized controlled trial in which high doses of n-3 PUFAs (EPA + DHA, 3.3 g/day) over a 6-month period did not decrease carotid intima-media thickness or other measures of vascular function (artery flow mediated dilatation) in patients with T1D [44]. Notwithstanding, it cannot be ruled out that very high doses (i.e., 4 g/day) of a specific n-3 PUFA (EPA) over a long time period (i.e., REDUCE-IT trial [45]) could be beneficial for CVD prevention in this specific high-risk population.…”
Section: Discussionsupporting
confidence: 91%
“…Detailed information regarding each study has been published previously [9,20]. In the present analysis, we included participants meeting the following inclusion criteria: classical presentation of T1D (including primary osmotic symptoms, weight loss, hyperglycaemia, ketosis, insulin initiation at diagnosis); aged 18-50 years; diagnosed with T1D for a minimum of 5-years on enrolment; treated on a stable (> 12-months) basal-bolus insulin regimen consisting of rapid-acting insulin analogues lispro or aspart and basal insulin glargine delivered through multiple daily injections or continuous subcutaneous insulin infusion; and free of diabetes-related complications.…”
Section: Methodsmentioning
confidence: 99%
“…A recent preliminary trial investigating the effects of omega-3 in adults with type 1 diabetes demonstrated no significant changes in vascular health, glucose hemostasis, and metabolic parameters. However, limitations of the mentioned study including relatively small sample size, high number of subjects lost to follow-up, and the broad selection of people with different treatment regimens and duration of disease may cause bias in obtained results [ 21 ]. Another study performed by Casanova et al [ 22 ] concluded that omega-3 supplementation improved arterial stiffness and endothelial function in hypertensive patients with high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%